Inherited disorders of the neuromuscular junction: an update. - Rodríguez Cruz, P; Palace, J; Beeson, D (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2014)
Congenital myasthenic syndromes (CMSs) are a group of heterogeneous inherited disorders caused by mutations in genes affecting the function and structure of the neuromuscular junction. This review updates the reader on established and novel subtypes of congenital myasthenia, and the treatment strategies for these increasingly heterogeneous disorders. The discovery of mutations associated with the N-glycosylation pathway and in the family of serine peptidases has shown that causative genes encoding ubiquitously expressed molecules can produce defects at the human neuromuscular junction. By contrast, mutations in lipoprotein-like receptor 4 (LRP4), a long-time candidate gene for congenital myasthenia, and a novel phenotype of myasthenia with distal weakness and atrophy due to mutations in AGRN have now been described. In addition, a pathogenic splicing mutation in a nonfunctional exon of CHRNA1 has been reported emphasizing the importance of analysing nonfunctional exons in genetic analysis. The benefit of salbutamol and ephedrine alone or combined with pyridostigmine or 3,4-DAP is increasingly being reported for particular subtypes of CMS.